ANALISIS PENGELOLAAN OBAT DI INSTALASI FARMASI RSUD. Dr. H. MOCH. ANSARI SALEH BANJARMASIN - Noor Aisyah; Nanda Oktaviani; Abdul Mahmud Yumassik; Amaliyah Wahyuni; Roseyana Asmahanie (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Optimal drug management is essential because stock shortages or surpluses can affect hospital service costs. This study aimed to determine the percentage of planning achievement, invoice errors, procurement frequency per drug item, and the percentage of dead stock, expired, and damaged drugs at Dr. H. Moch Ansari Saleh Regional General Hospital, Banjarmasin. This study was a descriptive, observational, non-experimental research with a cross-sectional design using retrospective data, analyzed quantitatively and presented descriptively. The population consisted of all pharmaceutical supply management data from 2024. Samples were obtained using a total sampling technique, covering data on planning, procurement, receipt, storage, and control. Observation sheets were used as instruments, and data were processed using Microsoft Excel. The results showed a planning achievement rate of 86.06%. Invoice errors were 0%, meeting the standard. Out of 484 drug items, procurement frequency consisted of 279 low-frequency, 196 medium-frequency, and 9 high-frequency items. The percentage of dead stock was 3.37%, while expired and damaged drugs accounted for 0.02%, meeting the standard of less than 1.